Mining for justice : a Chloe Ellefson mystery - Ernst, Kathleen, 1959- (Ernst, Kathleen, 1959- Chloe Ellefson mystery., 2017)
Chloe Ellefson is excited to be learning about Wisconsin's Cornish immigrants and mining history while on temporary assignment at Pendarvis, a historic site in charming Mineral Point. But when her boyfriend, police officer Roelke McKenna, discovers long-buried human remains in the root cellar of an old Cornish cottage, Chloe reluctantly agrees to mine the historical record for answers. She soon finds herself in the center of a heated and deadly controversy that threatens to close Pendarvis. While struggling to help the historic site, Chloe must unearth dark secrets, past and present . . . before a killer comes to bury her. Praise: "Richly imagined and compelling, Mining for Justiceonce again highlights Kathleen Ernst's prowess as a storyteller, with its nuanced characters and intersecting mysteries . . . Ernst is a master of reconstructing the past, providing vivid and authentic details about the lives of early Cornish immigrants in Wisconsin, while showing how the secrets of those long-buried people still matter in the present day."--Susanna Calkins, author of the Macavity-winning Lucy Campion Mysteries